Gender and Social Isolation across the Life Course - Umberson, Debra; Lin, Zhiyong; Cha, Hyungmin (Journal of health and social behavior, 2022)
Social isolation has robust adverse effects on health, well-being, dementia risk, and longevity. Although most studies suggest similar effects of isolation on the health of men and women, there has been much less attention to gendered patterns of social isolation over the life course—despite decades of research suggesting gender differences in social ties. We build on theoretical frames of constrained choice and gender-as-relational to argue that gender differences in isolation are apparent but depend on timing in the life course and marital/partnership history. Results indicate that boys/men are more isolated than girls/women through most of the life course, and this gender difference is much greater for the never married and those with disrupted relationship histories. Strikingly, levels of social isolation steadily increase from adolescence through later life for both men and women.